Synthesis and Characterization of New Metal Complexes of [N-acetyl (amino)thioxo methyl] Glycine - Naema, Ban Z (Al-Nahrain Journal of Science, 2018)
A new Ligand (ATG)(N-acetyl amino thioxomethyl) Glycine was prepared by the reaction of acetyl iso thiocyanate with Glycine, The Ligand was characterized by FT-IR, UV-vis and 1HNMR, some complexes of the ligand were synthesized and characterized by FT-IR, UV-vis spectra, move over determination of metal content by Flame atomic absorption spectroscopy, molar conductance in DMSO solution and magnetic moments(μeff).